INTERACTION OF EXPERIENTIAL & BUZZ MARKETING, MASLOW NEEDS THEORY TO CONSUMER PURCHASE INTENTION JD.ID DURING PANDEMIC COVID-19. - Bestari, Dinda Kayani Putri; rahay, Ariska sri; Ainunnisa, Shafira Febrianti; Permatasari, Luvi Indha; R, Erfani Rahmasania; Nuraziza, Tasya (CENTRAL ASIA AND THE CAUCASUS, 2022)
The impact of the Covid-19 pandemic, one of which is the decline in social welfare which directly affects people's purchasing power. Every effort has been made so that the economy can bounce back, so far it is in a condition that tends to increase and the economy is starting to rise. This situation benefits all parties, including e- commerce business players in Indonesia, there are six e-commerce displays that have been able to survive the Covid-19 pandemic, one of which is JD.ID. Currently, JD.ID's business development is still far behind compared to Shopee, Tokopedia and Bukalapak. Therefore, this study was conducted to see the magnitude of the predicted interaction formed from experiential marketing, buzz marketing, fulfillment of needs based on Maslow's theory of people's buying interest in JD.ID E- Commerce. In the study there were 72 samples who were domiciled in West Java. Quantitative analysis is processed using Partial Least Square (PLS) tools. The results of the study state that buzz marketing has a significant effect on consumer purchase intention. Then Exp. Marketing has a significant effect on buzz marketing,this indicates that the better a person's shopping experience will be, it will have an effect on increasing engagement with JD.ID. Next Exp. Marketing has no significant effect on Con. Purchase Intention Then Maslow's Hierarchy has no significant effect on Buzz Marketing, this indicates that a person's need for something cannot influence a person or individual to suggest or provide information about the JD.ID application to other individuals. And finally, Maslow's Hierarchy has a significant effect on Con. Purchase Intentions.